2004
DOI: 10.1364/opex.12.002120
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of high-aspect ratio, micro-fluidic channels and tunnels using femtosecond laser pulses and chemical etching

Abstract: We present novel results obtained in the fabrication of high-aspect ratio micro-fluidic microstructures chemically etched from fused silica substrates locally exposed to femtosecond laser radiation. A volume sampling method to generate three-dimensional patterns is proposed and a systematic SEM-based analysis of the microstructure is presented. The results obtained gives new insights toward a better understanding of the femtosecond laser interaction with fused silica glass (a-SiO(2)).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
270
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 457 publications
(279 citation statements)
references
References 11 publications
(25 reference statements)
8
270
0
1
Order By: Relevance
“…5,9 The effect of nanograting formation has already found numerous applications for polarization control devices [10][11][12] and microfluidics. 13 More recently, the subwavelength nanostructures were also proposed for rewritable polarization multiplexed optical memory, 14 where the information encoding would be realized by means of two birefringence parameters, i.e. the slow axis orientation (4th dimension) and strength of retardance (5th dimension), in addition to three spatial coordinates.…”
mentioning
confidence: 99%
“…5,9 The effect of nanograting formation has already found numerous applications for polarization control devices [10][11][12] and microfluidics. 13 More recently, the subwavelength nanostructures were also proposed for rewritable polarization multiplexed optical memory, 14 where the information encoding would be realized by means of two birefringence parameters, i.e. the slow axis orientation (4th dimension) and strength of retardance (5th dimension), in addition to three spatial coordinates.…”
mentioning
confidence: 99%
“…Hence, complex structures can be directly written in materials, such as pure silica, that are traditionally challenging for standard direct laser processing. Furthermore, depending on the laser intensity and the material utilized, different features with either positive or negative index change, or voids, can be realized in the bulk of the irradiated material, thus targeting numerous applications such as waveguides, 2 Bragg gratings, 3 diffraction optics, 4 microfluidic channels, 5 and data storage. 6 It has been shown that femtosecond laser writing in wide band gap materials can induce an optically isotropic positive index change 1 as high as 3 ϫ 10 −2 ͑type I_fs͒.…”
mentioning
confidence: 99%
“…3 shows an illustration of the matrix ablation and an example of obtained U-groove. The desired section pattern of the groove is applied to the substrate by writing adjacent lines, which define a matrix in the transverse (X, Z) plane [23]. The U-groove with length 200 mm, width 40 mm and depth 50 mm was made by inscribing a volume consisting of a matrix of (20 Â 10) lines at a speed of 1 mm/ s and pulse energy of 2 mJ, and matrix density parameters (DX, DZ) were chosen to be respectively 2 mm and 1 mm.…”
Section: Resultsmentioning
confidence: 99%